Associations between clinical benefits of cancer drugs and incremental quality-adjusted life years used in reimbursement decisions in Australia, Canada, England and China: an observational study - Feng Xie; Dawei Zhu; Xiaodong Guan; Luwen Shi; Sheng Han; Yichen Zhang; Jinyu Chen; Kexin Han (BMJ Open)
Objectives To investigate the association between incremental quality-adjusted life years (QALYs) predicted in economic evaluations and clinical benefits assessed by the European Society for Medical Oncology-Magnitude of Clinical Benefit Scale (ESMO-MCBS), examining how accurately predicted QALYs reflect actual clinical outcomes in cancer drug reimbursement decisions.Design Cross-sectional observational study.Setting Health technology assessment (HTA) documents from Australia, Canada and England, supplemented by published economic evaluations from China. Economic evaluation data were collected from database inception to 31 December 2023.Participants A total of 240 economic evaluation documents were identified from Australia (n=61), Canada (n=114) and England (n=65), along with 106 published studies from China, all focused on solid tumour cancer drugs with publicly available ESMO-MCBS scores. Documents were included based on completeness and consistency of data sources; those that were incomplete or relied on external controls were excluded.Primary and secondary outcome measures The primary outcomes were the incremental QALYs from manufacturer submissions and HTA agency reevaluations. Secondary outcomes included associations stratified by data maturity, country, treatment setting and reimbursement recommendations.Results Incremental QALYs showed a moderate positive correlation with ESMO-MCBS scores (Spearman’s ρ=0.42, 95% CI: 0.31 to 0.53). All country-specific correlations were statistically significant: England (ρ=0.53), Australia (ρ=0.37), Canada (ρ=0.39) and China (ρ=0.49), all p<0.01. Stronger associations were observed in HTA agency reevaluations (adjusted OR=1.43, 95% CI: 1.15 to 1.77) compared with manufacturer submissions (OR=1.21, 95% CI: 1.09 to 1.34). Analyses limited to mature data (>70% events observed) demonstrated the strongest association (OR=1.53, 95% CI: 1.10 to 2.13). Among countries, England exhibited the highest association (OR=1.42, 95% CI: 1.15 to 1.74), followed by China (OR=1.30, 95% CI: 1.04 to 1.62), Australia (OR=1.28, 95% CI: 1.01 to 1.63), and Canada (OR=1.15, 95% CI: 1.05 to 1.26).Conclusions This study highlights a moderate alignment between incremental QALYs derived from economic evaluations and clinical benefit scores, emphasising the importance of rigorous reassessment, mature survival data and independent validation processes. Future research should explore strategies for enhancing data maturity and incorporating independent review mechanisms to strengthen healthcare decision-making globally.